2007
DOI: 10.1161/circresaha.107.150474
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Endothelial Cell–Specific NF-κB Suppression Attenuates Hypertension-Induced Renal Damage

Abstract: Abstract-Nuclear factor kappa B (NF-B) participates in hypertension-induced vascular and target-organ damage. We tested whether or not endothelial cell-specific NF-B suppression would be ameliorative. We generated Cre/lox transgenic mice with endothelial cell-restricted NF-B super-repressor IB␣⌬N (Tie-1-⌬N mice) overexpression. We confirmed cell-specific IB␣⌬N expression and reduced NF-B activity after TNF-␣ stimulation in primary endothelial cell culture. To induce hypertension with target-organ damage, we fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
94
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(106 citation statements)
references
References 45 publications
10
94
0
2
Order By: Relevance
“…Hu et al (13) demonstrated that the administration of pressor doses of L-NAME (10 g·kg Ϫ1 ·min Ϫ1 ) in combination with a small dose of ANG II (10 ng· kg Ϫ1 ·min Ϫ1 ) in rats exacerbated both the hypertension and renal injury compared with rats made hypertensive with L-NAME or ANG II alone; however, the magnitude of BP-dependent vs. BPindependent renal injury was not determined. Particularly relevant to the results of our study, Henke et al (12) reported that suppression of endothelial NF-B, a master regulatory transcription factor influencing several potential pathways of injury (i.e., oxidative stress, inflammation, etc.) attenuated renal injury in ANG IIϩL-NAME-induced hypertensive mice fed a 1% NaCl diet.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Hu et al (13) demonstrated that the administration of pressor doses of L-NAME (10 g·kg Ϫ1 ·min Ϫ1 ) in combination with a small dose of ANG II (10 ng· kg Ϫ1 ·min Ϫ1 ) in rats exacerbated both the hypertension and renal injury compared with rats made hypertensive with L-NAME or ANG II alone; however, the magnitude of BP-dependent vs. BPindependent renal injury was not determined. Particularly relevant to the results of our study, Henke et al (12) reported that suppression of endothelial NF-B, a master regulatory transcription factor influencing several potential pathways of injury (i.e., oxidative stress, inflammation, etc.) attenuated renal injury in ANG IIϩL-NAME-induced hypertensive mice fed a 1% NaCl diet.…”
Section: Discussionsupporting
confidence: 62%
“…), and it has become well established that nitric oxide (NO) plays an important role to counterbalance these deleterious pathways (1). Elevated ANG II and decreased NO levels have been reported in models of diabetes, heart failure, atherosclerosis, and hypertension (1,12,19,33,38,48). It is possible that the extent of BP-independent injury induced by ANG II would be exacerbated in situations of reduced NO availability.…”
mentioning
confidence: 99%
“…In rats, the suppression of endothelial NF-kB, measured by IHC, showed a decrease in renal injuryinduced arterial hypertension [7]. In human renal disease, there has not been any histologic evidence of NFkB activation in vascular cells [10,11,17,22].…”
Section: Discussionmentioning
confidence: 98%
“…This pathway seems to play a central role in blood pressure control since its blockade protects against hypertension (67). NF-κB activation within the vascular endothelium drives hypertensive renal damage without measurable effects on blood pressure suggesting a direct role in end-organ damage (68). Within cardiovascular control centers in the brain, NF-κB activation potently enhances sympathetic outflow (69)(70)(71), which could potentially promote sodium retention in the kidney via stimulation of renal sympathetic nerves.…”
Section: Immune Mechanisms In Hypertensionmentioning
confidence: 99%